The Environmental Creditworthiness Assessment Methodology - Čančer, Vesna; Rebernik, Miroslav; Knez-Riedl, Jožica (Naše gospodarstvo/Our economy, 2013)
This paper aims to offer a review of existing theoretical bases of the measurement and assessment of environmental creditworthiness, particularly on the level of en- terprises. Its objective is also to examine the possibilities of the multicriteria assessment of environmental creditworthiness by enterprises themselves (“internal rating”). Following the prescriptive approach, it delineates the particularities of a frame procedure for the multi-criteria assessment of environmental creditworthiness. The credibility of ecoratings depends not only on the quality of information sources and the choice of sensible environmental indicators, but also on the transformation of data into local and aggregate values that are understandable to decision makers.
Keywords: environmental creditworthiness assessment; enterprise; multi-criteria decision making; prescriptive approach; social responsibility